Do Borrowing Constraints Change U.S. Homeownership Rates? - Linneman, Peter; Megbolugbe, Isaac F.; Wachter, Susan M.; Cho, Man (Journal of Housing Economics, 1997)
This study has two main objectives. First, we estimate various alternative specifications of the tenure choice model with borrowing constraint variables, originally put forth by Linneman and Wachter, using a more recent sample of the Survey of Consumer Finance. Second, we simulate effects of policy changes governing constraints and changes in mortgage interest rates, both on households' owning decisions and on the aggregate homeownership rate. While the impact of constraints has been demonstrated in previous studies, our research provides the first microsimulation estimates of the impact for aggregate homeownership rates for the entire U.S. population.